Moisture Sorption Characteristics of Weaning Food - Bhattarai, Kabindra; Adhikari, Babita; Ghimire, Prabina (Himalayan Journal of Science and Technology, 2020)
Stickiness and caking are the significant problems for food powders due to moisture migration from the storage environment. This study was conducted to determine the moisture sorption isotherm of weaning food (Nutrilac and Superceral) and to fit the sorption data in different sorption isotherm models. Static gravimetric method was used to determine the equilibrium moisture content (EMC) at 22-89% RH at 30°C. The EMC data obtained were plotted to the models Brunauer Emmet Teller (BET), Guggenheim Anderson and De Boer (GAB). Results indicated that sorption isotherms were of type II isotherm according to Brunauer et al., (1940) classification. BET model was fitted to the sorption data with coefficient of regression 0.985 and 0.986 for Nutrilac and Supercereal respectively. The GAB model was fitted with coefficient of regression 0.983 and 0.979 for Nutrilac and Supercereal respectively. Monolayer moisture content determined from the BET and GAB model at 30°C were 1.63 and 2.24 g/100g dry matter for Nutrilac and 1.51 and 2.26 g/100g dry matter for Supercereal respectively.